Development and validation of the SIMPLE endoscopic classification of diminutive and small colorectal polyps - Iacucci, Marietta; Trovato, Cristina; Daperno, Marco; Akinola, Oluseyi; Greenwald, David; Gross, Seth A.; Hoffman, Arthur; Lee, Jeffrey; Lethebe, Brendan C.; Lowerison, Mark; Nayor, Jennifer; Neumann, Helmut; Rath, Timo; Sanduleanu, Silvia; Sharma, Prateek; Kiesslich, Ralf; Ghosh, Subrata; Saltzman, John R.; and the SIMPLE classification investigator team (Endoscopy, 2018)
Background Prediction of histology of small polyps facilitates colonoscopic treatment. The aims of this study were: 1) to develop a simplified polyp classification, 2) to evaluate its performance in predicting polyp histology, and 3) to evaluate the reproducibility of the classification by trainees using multiplatform endoscopic systems. Methods In phase 1, a new simplified endoscopic classification for polyps – Simplified Identification Method for Polyp Labeling during Endoscopy (SIMPLE) – was created, using the new I-SCAN OE system (Pentax, Tokyo, Japan), by eight international experts. In phase 2, the accuracy, level of confidence, and interobserver agreement to predict polyp histology before and after training, and univariable/multivariable analysis of the endoscopic features, were performed. In phase 3, the reproducibility of SIMPLE by trainees using different endoscopy platforms was evaluated.Results Using the SIMPLE classification, the accuracy of experts in predicting polyps was 83 % (95 % confidence interval [CI] 77 % – 88 %) before and 94 % (95 %CI 89 % – 97 %) after training (P  = 0.002). The sensitivity, specificity, positive predictive value, and negative predictive value after training were 97 %, 88 %, 95 %, and 91 %. The interobserver agreement of polyp diagnosis improved from 0.46 (95 %CI 0.30 – 0.64) before to 0.66 (95 %CI 0.48 – 0.82) after training. The trainees demonstrated that the SIMPLE classification is applicable across endoscopy platforms, with similar post-training accuracies for narrow-band imaging NBI classification (0.69; 95 %CI 0.64 – 0.73) and SIMPLE (0.71; 95 %CI 0.67 – 0.75).Conclusions Using the I-SCAN OE system, the new SIMPLE classification demonstrated a high degree of accuracy for adenoma diagnosis, meeting the ASGE PIVI recommendations. We demonstrated that SIMPLE may be used with either I-SCAN OE or NBI.